Peran Mediasi Customer Engagement Pada Pengaruh Content Marketing Dan Influencer Marketing Terhadap Purchase Decision (Kasus Pengguna Bedak Padat Pixy Pada Platform Tiktok di Kota Tangerang) - Ayu Aini; Lutfi Lutfi; Diqbal Satyanegara (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2025)
Social media has become an important platform for cosmetic companies to implement marketing strategies and reach wider consumer markets. This study examines the mediating role of Customer Engagement in the relationship between Content Marketing, Influencer Marketing, and Purchase Decisions among Pixy compact powder users on TikTok in Tangerang City. Using a quantitative approach, data were collected from 162 respondents and analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. The results indicate that Content Marketing has a negative and insignificant effect on Purchase Decisions but a positive and significant effect on Customer Engagement. Influencer Marketing positively and significantly affects both Purchase Decisions and Customer Engagement. Customer Engagement also has a positive and significant effect on Purchase Decisions. Furthermore, Customer Engagement fully mediates the effect of Content Marketing on Purchase Decisions and partially mediates the effect of Influencer Marketing on Purchase Decisions.